An Empirical Study of Disclosure Practices in Listed Non-Financial Indian Companies - Bapat, Varadraj; Raithata, Mehul (Prabandhan: Indian Journal of Management, 2010)
Corporate transparency and disclosures have gained a lot of momentum in the corporate word since the past few decades. It has become essential for the long-term survival and success of a business. The demand for corporate information emanates from different stakeholders, particularly the financial stakeholders. Information asymmetry between a firm's management and financial stakeholders, equity shareholders and bondholders, call for higher transparency and better disclosure in mitigating the agency problem in corporate governance. Financial reporting and disclosure are a potentially important means for the management to communicate a firm's performance and governance to outside investors. As disclosure improves efficiency of capital allocation and also reduces the cost of capital, almost all countries devote substantial resources in framing and regulating disclosure rules and governance structure that publicly traded firms must follow. The Organization for Economic Co-operation and Development (OECD) report on Corporate Governance and National Development (OECD, 2001) as well as the Asian Development Bank (ADB) study on Corporate Governance and Finance in East Asia (ADB, 2001) highlight recent efforts by many developing countries in improving corporate governance and disclosure structures.